A Combined Urogynaecological Approach for Pelvic Organ Prolapse: Results of a Rural Centre from Northern Maharashtra, India - Dhangar, Dr. Sanjay P.; Gosavi, Dr. Amrapali D.; Gite, Dr. Sushant S. (SP’z Series New Insights on Urology and Urological Research Part II, 2023)
Introduction: Pelvic organ prolapse (POP) is a benign condition that can turn symptomatically malignant, if not treated on time. A multidisciplinary combined approach is required to tackle this condition. Aim: Clinical diagnosis of women with POP, with genito-urinary symptoms and the options for their management under one roof and combined care of urologist and gynaecologist. Materials and Methods: This study was done in patients admitted with signs and symptoms of POP. The details regarding the age at the onset of genito-urinary symptoms, parity status, obstetric information and degree of POP were analysed and recorded. Results: Majority of the cases were manual labourers and farmers (70.1%). Majority of them 75.4% presented at 46-60 years of age. Inadequate birth spacing was noted in 33.33% cases. Deliveries conducted by untrained personnel were noted in 22.8% patients. History of prolonged labour was there in 21% cases. Most of the cases presented 78.9% as III rd degree U.V. prolapse with cystocele and/or enterocele. 42.1% patients had stress urinary incontinence. Hysterectomy with pelvic floor repair (PFR) was done 78.9% patients, tension free transobturator tape (TOT) repair with or without PFR was done in 15.7% patients. In the remaining 5.26% cases conservative management was advised. Conclusion: POP is one of the major urogynecologic problems in older rural women. Referral to pelvic floor clinics for multidisciplinary care can help in dealing the complex condition carefully in a simpler way for the benefit of the patients.